Effect of glycemic control and type of diabetes treatment on TB treatment outcomes among people with TB-diabetes: A systematic review (updated August 2024). - Hemant Deepak Shewade; Prabhadevi Ravichandran; S Satish; S Kiran Pradeep; Kathiresan Jeyashree; Preetam Mahajan; Amar N Shah; Richard Kirubakaran; Ajay M V Kumar (PLoS ONE, 2025)
Background Stringent glycemic control and/or using insulin either as a replacement for or in addition to oral hypoglycemic agents (OHAs) has been recommended for people with tuberculosis and diabetes mellitus (TB-DM). This systematic review (PROSPERO 2016:CRD42016039101) analyses whether this improves TB treatment outcomes. This is an updated review (up to August 2024) of a previously published systematic review (1996 - April 2017). Objectives Among people with drug-susceptible TB-DM on anti-TB treatment, to determine the effect of i) glycemic control (stringent or less stringent) compared to poor glycemic control and ii) insulin (only or with OHAs) compared to 'OHAs only' on unfavorable TB treatment outcome(s) at the end of intensive phase and/ or end of TB treatment (minimum six months and maximum 12 months follow up). Methods We conducted comprehensive searches across multiple databases (EMBASE, PubMed, Google Scholar, Cochrane Database of Systematic Reviews) and sources. Eligible studies included interventional and cohort studies examining people with TB-DM. Screening, data extraction and risk of bias assessment were done independently by two investigators and recourse to a third investigator, for resolution of differences. Results From a total of 7107 articles, we included 14 studies, with five added in this update (all observational cohort studies). Of 14, only one high-quality study reported that stringent glycemic control (HbA1c < 7% at baseline) was associated with lower risk of unfavorable treatment outcomes, including recurrence, compared to non-stringent and/or poor glycemic control. Other studies showed mixed results and had significant biases or were limited by sample size. The five newly included studies had a high risk of bias and did not provide clear evidence. Due to clinical and methodological heterogeneity, we did not perform a meta-analysis. Conclusion The updated review re-emphasizes the need for high-quality research on the effects of glycemic control and addition of insulin among people with TB-DM on TB treatment outcomes. We need well-designed randomized controlled trials, specifically for the effect of adding insulin on TB treatment outcomes. We discuss ten measures to guide well-designed cohort studies on this topic. Harmonization of the methods is needed and would facilitate comparisons.